Diseño de un sistema de control interno para las empresas productoras y explotadoras de balsa. Caso: empresa Produsiembal Cia. Ltda. - Ortiz Guamaní, Jaime Patricio (2010)
This research provides a model in which this can perform all its activities and processes in a more efficient way of providing for this timely and reliable systems.